Characterization of ionic liquid‐based biocatalytic two‐phase reaction system for production of biodiesel - Prabhavathi Devi, Bethala Lakshmi Anu; Guo, Zheng; Xu, Xuebing (AIChE Journal, 2011)
The property of a variety of ionic liquids (ILs) as reaction media was evaluated for the production of biodiesel by enzymatic methanolysis of rapeseed oil. The IL Ammoeng 102, containing tetraaminum cation with C18 acyl and oligoethyleneglycol units, was found to be capable of forming oil/IL biphasic reaction system by mixing with substrates, which is highly effective for the production of biodiesel with more than 98% biodiesel yield and nearly 100% conversion of oil. Conductor‐like screening model for real solvent (COSMO‐RS) in silico prediction of substrate solubility and simulation of partition coefficient change vs. reaction evolution indicated that the amphiphilic property of Ammoeng 102 might be responsible for creating efficient interaction of immiscible substrates; while big difference of partition coefficients of generated biodiesel and glycerol between the two phases suggests a large chemical potential to move reaction equilibrium for maximum oil conversion and yield of target biodiesel. The reaction behavior and specificity of oil/IL biphasic system for enzymatic production of biodiesel were theoretically delineated through COSMO‐RS computation with experimental validation. © 2010 American Institute of Chemical Engineers AIChE J, 2011